Deteksi Dini Prokrastinasi Akademik melalui Regulasi Diri dan Peran Bimbingan dan Konseling - Zafirah Talitha Arisyah; Hijr Amelya; Habibila Salwa Jenny; Fadilianti Maghfiroh; Della Donauli Simanjuntak; Rizki Novirson (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Academic procrastination is the behavior of deliberately delaying the completion of tasks even though individuals are aware of the negative consequences for their learning outcomes. This phenomenon is commonly found among students at various educational levels, ranging from secondary school to higher education, and often results in decreased academic achievement, lower quality of completed assignments, and increased levels of academic stress among students. This condition indicates that academic procrastination has become an important issue that requires attention within the educational process. This study aims to examine self-regulation as an indicator for the early detection of academic procrastination in the context of guidance and counseling services in educational settings. The method used in this study is a literature review by analyzing various scientific journal articles relevant to the research topic. The results of the review show a consistent negative relationship between self-regulation and academic procrastination. Students who possess a high level of self-regulation tend to be more capable of managing their time, emotions, and learning motivation effectively, enabling them to be more disciplined in completing academic tasks. Conversely, low levels of self-regulation contribute to an increased tendency to delay academic tasks. These findings confirm that self-regulation can serve as a strategic indicator for early detection as well as a target for preventive interventions through guidance and counseling services in schools.